(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2020)
Autobiographic text: Giacomo Verde was born in the province of Naples in 1956 and gained a diploma in textile arts at the Art Institute of Florence. Since 1973 he has dedicated himself to the theatre and the arts as author, actor, musician, director. His video productions date back to 1983 and combine attention to "poor" media and materials and the theatrical tradition with an experimentalism that is both eclectic and critical of the new electronic technologies. He has invented "tele-tales" (tele-racconto) for children (performance that unites narration, micro-theatre and macro-video live), worked with prison inmates, animated ’Euclid’, the interactive artificial puppet of Studio Azzurro, created "poor" and alternative games for using television intelligently, founded the SeStessiVideo production company, taught how to destroy television sets, written, polemicized, invented formulae and definitions. He defines himself as a "teknoartist" and he’s engaged in interactive art.